Increased Utilization of Primary Health Care Centers for Birthing Care in Tamil Nadu, India: A Visible Impact of Policies, Initiatives, and Innovations - Pandian, Jayanthi (J Family Med Prim Care, 2013)
BACKGROUND: Tamil Nadu has been showing an increasing trend in institutional deliveries since early 1990's and has now achieved near 100%. Among the institutional deliveries, a change was observed since 2006, wherein primary health centers (PHCs) showed a four-fold increase in deliveries, while other public and private health facilities showed a decline, despite equal access to all categories of health facilities. What led to this increased utilization of PHCs for birthing care? MATERIAL AND METHODS: Policies, documents, and published reports of the Government of Tamil Nadu (GoTN) were reviewed and interviews were conducted with the various stakeholders involved in providing birthing care in the PHCs. This study analyzes the impact of the policies and supply side initiatives and innovations which led to increase utilization of the PHCs for birthing care. RESULTS: Scaling up of 24 × 7 services in all PHCs, upgrading PHCs with good infrastructure, human resources, and women friendly services have helped to boost the image of the PHCs. Pro-women policies like maternity benefit schemes, birth companionship, providing food, and compulsory stay for 48 h following delivery have attracted women towards PHC. Innovative strategies like maternity picnics and use of expected date of delivery (EDD) chart for follow-up have made women choose PHCs, while periodic reviews and support to staff has improved service delivery. CONCLUSION: Women centered policies, efficient managerial systems, quality care, and innovative marketing of services have together contributed to increased utilization of PHCs for birthing. Other states could explore the possibility of replicating this model to make optimal use the PHC facilities.